Evaluating the Integration of Islamic Values in Primary Education: A Logic Model Approach - Tsani, Iskandar; Sufirmansyah, Sufirmansyah; Makmur, Makmur; In’am, Akhsanul (Jurnal Pendidikan Islam, 2024)
This study examined the acquisition of Islamic values in an Islamic primary school using a logic model-based evaluative approach to assess input, output, and outcome dimensions. The research aimed to evaluate the effectiveness of educational practices in promoting Islamic values among students. Data were gathered through interviews, observation, and documentation, and were analyzed through iterative stages of collection, reduction, display, and conclusion. Findings indicate that the structural input for Islamic values learning involves coordinated efforts among various school departments. The school's cultural climate excels in academic, communal, security, and institutional areas. The output is reflected in diverse activities such as morning murÃ¢jaâ€™ah sessions, Quran reading and writing guidance using the Ummi method, congregational prayers, and rituals like Clean Friday and Blessed Friday. These activities lead to outcomes that foster individual piety, integrity, discipline, honesty, responsibility, creativity, and social consciousness among students. The study underscores the importance of instilling Islamic values from an early age, highlighting its potential to foster lifelong adherence to these principles. In conclusion, the research affirms the efficacy of these educational practices in transmitting Islamic values, emphasizing the pivotal role of primary education in cultivating a deep-rooted commitment to these values for the future.